Velhice e violência na esfera judiciária no estado do Tocantins - Otsuka, José Kasuo (2010)
The origins of this present investigation came from the need for a theoretical and methodological immersion about problems inside the Gerontology and the Law relationship like interdisciplinary exercise. The concrete evidences roots of this study are concentrated in the quest about the understanding the phenomenon of absencepresence and (in) visibility of law practices from of elderly people in the Judiciary staff in Palmas, Tocantins brazilian province. Palmas is the fifth highest incidence of deaths from unnatural causes among the elderly by search results point in the national researches. Phenomena like violence, abandonment, effectiveness of public policies absence directed to older people sometimes invisible or visible on purpose occurs. To understand this phenomenon and design the combat actions from the Legal Field is the problem of it research. The methodologic work with the researches feedback contributions who use as support historical criticism and hermeneutics optics. From the contribution of historians, sociologists, philosophers, educators, and many researchers that fight to transform the Gerontology as a field of study and action could rise by the documents, bibliographies and cleavage violence in the legal actions direct for to the oldest people, and the same time search these operation and results. Tocantins results like a hybrid space constructed by the associations adopted in the political arena, full of invisible borders demarcated by groups of stakeholders representatives of the economic, cultural, political, religious, educational and law. How is tackled in this hybrid society from the field of law about violence against the elderly? Where are the visible practices and why public policies seem to be silenced? The exploratory aspect study is necessary because it is a first-year academic diligence on the applicability of laws among the elderly from the phenomenon of violence. In exploratory evidence implies to reveal the phenomena like a corpus legalis and it locus, the Judiciary Field. And the other loci of divers fields who presume to act in the fighting and prevention. For the constant reflection exercise hunched over documents, police reports and the ordinary pressure to solve practical everyday problems are important signals about - how to work with the multi-referential approach in the Judiciary Field and even the attempts to establish an Interdisciplinary help relation to the Law and Gerontology in combat of violence against the elderly